Fractal Dimension Calculation for the General Shapes of ‎Geographical Maps and Closed Curves - Rayan Alkhayat; Basil Thanoon (Al-Rafidain Journal of Computer Sciences and Mathematics)
This research includes building a software to calculate the Fractal Dimension of the general shapes of the borders of geographical maps as well as closed curves. Two methods are adopted for calculating fractal dimension: the first is the well-known Box Counting method and the second is Two-dimension Variation method , some treatments of the two methods are performed in order to qualify them for practical application and fitness for the use in digital images which are used for the representation of borders of maps and closed curves. Matlab 6.5 programming language was used for the implementation of this work, the map of the republic of Iraq was used as a case study for the given work.